An exploration of the causal relationship between 731 immunophenotypes and osteoporosis: a bidirectional Mendelian randomized study - Zhou, Dongqi; Zi, Changyan; Gan, Gaofeng; Tang, Shiyun; Chen, Qiu (Frontiers in Endocrinology, 2024)
Background: There are complex interactions between osteoporosis and the immune system, and it has become possible to explore their causal relationship based on Mendelian randomization methods.Methods: Utilizing openly accessible genetic data and employing Mendelian randomization analysis, we investigated the potential causal connection between 731 immune cell traits and the risk of developing osteoporosis.Results: Ten immune cell phenotypes were osteoporosis protective factors and three immune cell phenotypes were osteoporosis risk factors. Specifically, the odds ratio (OR) of IgD+ CD24+ %B cell (B cell panel) risk on Osteoporosis was estimated to be 0.9986 (95% CI = 0.9978~0.9996, P<0.01). The OR of CD24+ CD27+ %B cell (B cell panel) risk on Osteoporosis was estimated to be 0.9991 (95% CI = 0.9984~0.9998, P = 0.021). The OR of CD33-HLA DR+AC (Myeloid cell panel) risk on Osteoporosis was estimated to be 0.9996 (95% CI = 0.9993~0.9999, P = 0.038). The OR of EM CD8br %CD8br (Maturation stages of T cell panel) risk on Osteoporosis was estimated to be 1.0004 (95% CI = 1.0000~1.0008, P = 0.045). The OR of CD25 on IgD+ (B cell panel) risk on Osteoporosis was estimated to be 0.9995 (95% CI = 0.9991~0.9999, P = 0.024). The OR of CD25 on CD39+ activated Treg+ (Treg panel) risk on Osteoporosis was estimated to be 1.001 (95% CI = 1.0001~1.0019, P = 0.038). The OR of CCR2 on CD62L+ myeloid DC (cDC panel) risk on Osteoporosis was estimated to be 0.9992 (95% CI = 0.9984~0.9999, P = 0.048). The OR of CCR2 on CD62L+ plasmacytoid DC (cDC panel) risk on Osteoporosis was estimated to be 0.9993 (95% CI = 0.9987~0.9999, P = 0.035). The OR of CD45 on CD33dim HLA DR+ CD11b-(Myeloid cell panel) risk on Osteoporosis was estimated to be 0.9988 (95% CI = 0.9977~0.9998, P = 0.031). The OR of CD45 on Mo MDSC (Myeloid cell panel) risk on Osteoporosis was estimated to be 0.9992 (95% CI = 0.9985~0.9998, P = 0.017). Conclusions: Our study identified 13 unreported immune phenotypes that are causally related to osteoporosis, providing a theoretical basis for the bone immunology doctrine.